Investigating EFL Students' Capabilities in Grammatical Articles for Second Language Communicative Competence at an Indonesian Higher Education Context - Muhammad Fiqih Oktavian Hattah; Rusdiah Rusdiah; Ratnawati Ratnawati (Tamaddun Life, 2021)
The study aims to determine the ability to use English Articles by ABA UMI students and classify the types of difficulties in using English Articles by ABA UMI students. The study was conducted at ABA UMI using Google Form with a sample of 35 students. Data collection techniques through Interviews and essay tests were analyzed qualitatively. The results showed that the average number of students' correct answers from 20 questions was 12,1 questions or 60,71%. The average value obtained is 60,57. The Classification of students' abilities is in the "Good" category. The greatest difficulty of ABA students is in using article A, an average of 19,7/20 students (56,29%) answered correctly, and 15,3/15 students (43,71%) answered incorrectly from 6 questions related to article A. Most of the students answered article An for article A. On average, 23,7/24 students (67,71%) answered correctly, and 11,3/11 students (32,29%) answered incorrectly out of 7 questions in Article An. Students still have difficulty using articles A, An, and The. On average, 20 students (57,14%) gave correct answers, and 15 students (42,86%) answered incorrectly out of 7 questions for the article The. It can be concluded that the average ABA students are still quite difficult (39,62%) in understanding and using articles A, An and The.